2017
DOI: 10.1159/000475757
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ceftiofur on Hyperalgesia and Allodynia in a Rat Neuropathic Pain Model: The Role of Immune Processes

Abstract: Objective: Inflammatory and immune mechanisms play important roles in the pathogenesis of neuropathic pain. Ceftiofur, a third-generation cephalosporin, has anti-inflammatory effects by inhibiting tumor necrosis factor (TNF)-α, interleukin (IL)-1β, nuclear factor (NF)-κB, and mitogen-activated protein kinase (MAPK) signaling. This study aimed to investigate the effect of ceftiofur on hyperalgesia and allodynia in neuropathic rats and to define the possible contribution of immune mechanisms to this effect. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Our results demonstrated that PAR4 activation decreased tryptase, IL-1 β , iNOS, and P2X7 at the protein and mRNA levels in association with the regulation of p38 and ERK1/2 phosphorylation. The suppression of these inflammatory mediators through regulation by MAPK signals after the PAR4-AP treatment of the BMMCs provided a molecular mechanism for the inhibition of visceral hypersensitivity [ 33 , 34 ]. However, additional evidence is needed, and related interesting questions, for example, questions concerning interactions or crosstalk with inflammatory mediators, are worthy of further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrated that PAR4 activation decreased tryptase, IL-1 β , iNOS, and P2X7 at the protein and mRNA levels in association with the regulation of p38 and ERK1/2 phosphorylation. The suppression of these inflammatory mediators through regulation by MAPK signals after the PAR4-AP treatment of the BMMCs provided a molecular mechanism for the inhibition of visceral hypersensitivity [ 33 , 34 ]. However, additional evidence is needed, and related interesting questions, for example, questions concerning interactions or crosstalk with inflammatory mediators, are worthy of further investigation.…”
Section: Discussionmentioning
confidence: 99%